2020
DOI: 10.7717/peerj.9682
|View full text |Cite
|
Sign up to set email alerts
|

Generalized joint hypermobility among school-aged children in Majmaah region, Saudi Arabia

Abstract: Generalized joint hypermobility (GJH) is common among schoolchildren and usually benign. However, it may progressively lead to joint pain and developmental delay. Identifying GJH in school-aged children would facilitate the monitoring of early changes and planning for early rehabilitative intervention. Epidemiological studies addressing the prevalence of GJH among children in the Gulf region and Arab ethnicity are lacking. Hence, we aimed to determine the prevalence, pattern, and factors associated with GJH am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…[6,17,[20][21][22]25,27,28] Others reported no gender difference. [18,19,24,26,29] In our study, the difference in the BS between girls and boys was significant and the prevalence of GJH in girls was higher than boys, but this difference was not significant. Two Turkish studies showed significant female dominance and another one reported no gender difference.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…[6,17,[20][21][22]25,27,28] Others reported no gender difference. [18,19,24,26,29] In our study, the difference in the BS between girls and boys was significant and the prevalence of GJH in girls was higher than boys, but this difference was not significant. Two Turkish studies showed significant female dominance and another one reported no gender difference.…”
Section: Discussionmentioning
confidence: 50%
“…[28] A study from Saudi Arabia reported the prevalence of GJH 15.2% (cut-off≥4) and 7.6% (cut-off≥6). [29] An Indian study reported 58.8% (cut-off≥4) and 44.4% (cut-off≥6) [30] An Australian study reported 48% (cut-off≥4) and 18.6 % (cut-off≥6). [6] The results of GJH in the United Kingdom were 19.2% (cut-off≥4) and 4.2% (cut-off≥6).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been established in the literature that, in general, females are more mobile than males, evidence of gender differences on the different Beighton items has not been conclusive in previous studies [ 9 , 12 , 20 , 29 ]. The inclusion of hands-on-floor as a joint hypermobility test has been debated, as it is highly influenced by training [ 4 ].…”
Section: Introductionmentioning
confidence: 90%
“…De Boer et al used a Beighton score cut-off of >4, >5, or >6 to identify GJH in a population of 245 Dutch children and reported varying prevalences of 34.1%, 22.5%, and 16.5%, respectively [ 11 ]. Furthermore, a study conducted among 303 Arab school-aged children identified 15.2% and 7.6% of the study population as hypermobile using a Beighton cut-off of ≥4 and ≥6, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case definitions are a crucial feature of public health surveillance systems ( Coggon, 1999 ). Failure to use case definitions complicates the interpretation of surveillance data and to postulate preventive measures ( Hirve et al, 2020 ; Sirajudeen et al, 2020 ). Lastly, earlier researchers also fail to include a postural evaluation component.…”
Section: Introductionmentioning
confidence: 99%